Effect Of Strength On Cotton And Blended Mattress Fabric Produced By Mechanical Processing System (Daffodil International University Journal of Science and Technology, 2011)
Mattress fabric is one time used fabric. It need not require for washing. In this perspective, a project was taken to replace 100% cotton mattress fabric instead of Jute-Cotton blended mattress fabric. It is seen that Jute: Cotton blended mattress fabric posses similar properties to the 100% cotton mattress fabric. Bursting strength is an important factor for mattress fabric. From the comparison result, it is also seen that the bursting strength of 80:20/Jute: Cotton blended mattress fabric is nearer to the 100% cotton mattress fabric. On the other hand, blended mattress fabric is cheaper than 100% Cotton mattress fabric. Hence, blended mattress fabric may be the replacement of 100% cotton mattress fabric. Keywords: Strength; Mattress; Jute-cotton Union; Mechanical; Warpwise; Waftwise; Bursting. DOI: http://dx.doi.org/10.3329/diujst.v6i2.9340 DIUJST 2011; 6(2): 11-13